2011
DOI: 10.1016/j.exer.2011.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced retinal pigment epithelium regeneration after injury in MRL/MpJ mice

Abstract: Regenerative medicine holds the promise of restoring cells and tissues that are destroyed in human disease, including degenerative eye disorders. However, development of this approach in the eye has been limited by a lack of animal models that show robust regeneration of ocular tissue. Here, we test whether MRL/MpJ mice, which exhibit enhanced wound healing, can efficiently regenerate the retinal pigment epithelium (RPE) after an injury that mimics the loss of this tissue in age-related macular degeneration. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 56 publications
(112 reference statements)
7
33
0
Order By: Relevance
“…Mammals largely fail to regenerate a functional RPE monolayer following injury (20,21). One exception to this is in "super healer" MRL/MpJ mice, which regenerate RPE within ~30 days after administration of mild doses of sodium iodate that cause central RPE degeneration (61). Beyond this, the mammalian RPE is incapable of regenerating after severe injuries (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammals largely fail to regenerate a functional RPE monolayer following injury (20,21). One exception to this is in "super healer" MRL/MpJ mice, which regenerate RPE within ~30 days after administration of mild doses of sodium iodate that cause central RPE degeneration (61). Beyond this, the mammalian RPE is incapable of regenerating after severe injuries (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest the latter possibility, and highlight the important role played by peripheral RPE: in mouse, a subpopulation of mature RPE cells in the periphery remain in the cell cycle and respond to microscopic photocoagulation injuries by proliferating at a higher rate than central RPE cells (27,70), while experiments in pig have shown that peripheral RPE cells respond to debridement of central RPE by proliferating (71). Indeed, preservation of the peripheral RPE is a prerequisite for successful RPE regeneration in the MRL/MpJ mouse model, which fails to regenerate RPE when high doses of sodium iodate cause degeneration of central and peripheral RPE (61,72). Finally, the discovery of a subpopulation of RPE stem cells (30) suggests that an endogenous regeneration-capable population of RPE cells could exist in the human eye, and these might be analogous to injury responsive cells in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the regenerative response of the RPE to sodium iodate injury is enhanced in the Murphy Roths Large mouse strain (MRL) or “healer mouse”, and is correlated with elevated proliferation in the damaged region (Xia et al, 2011). Improved regenerative responses have been observed in several different tissues in the MRL mouse (Heber-Katz et al, 2004), but it is not clear whether the enhanced regenerative potential is due to alterations in systemic responses to injury or to a cell-intrinsic advantage within the regenerative cells themselves.…”
Section: Overview Of Early Eye Development and Rpe Specificationmentioning
confidence: 99%
“…It is known that mammalian RPE can repair small lesions, but that larger-scale restoration is not possible or leads to over-proliferation and pathology (19). Some insight into the proliferative capacity of mammalian RPE has been gleaned from studies in mice (20,21) and cultured human RPE cells (22), while studies in regeneration-capable non-mammalian systems have focused largely on RPE-to-retina transdifferentiation within the context of understanding retinal regeneration (23,24).…”
Section: Introductionmentioning
confidence: 99%